Topical cream from Channa micropeltes (Giant Snakehead fish) oil for arthritis - Omar, Muhammad Nor; Zainuddin, Nur Aziyah; Yunus, Kamaruzzaman (2009)
The topical cream from giant snakehead fish oil has been developed using vegetable oil, surfactants and stabilizers. The cream in the form of water-in-oil emulsion is stable at room temperature for 6 months. The cream could be used to accelerate wound healing, moisturize dry skin and treat rheumatoid arthritis.